Paraspinal Gossypiboma (Textiloma) Mimicking a Soft Tissue Tumor - Krishnan, Prasad (Asian Journal of Neurosurgery, 2023)
Paraspinal textilomas are dreaded complications of spinal surgery and rarely reported in view of the medico-legal problems they may create. As many of them are asymptomatic and most are unreported, their true incidence is unknown. They must be kept in mind when re-operating for any mass lesion seen on magnetic resonance imaging in the vicinity of a previously operated spine. We present the case of a 40-year-old man found to have a textiloma as a result of a previous surgery, describe his imaging and histological findings, discuss the causes that might lead to the same, and enumerate preventive strategies to avoid such a complication.
Keywords: paraspinal gossypiboma; textiloma; complication; spinal surgery; retained foreign body